Modern treatment of vulvar cancer - Merlo, Sebastjan (Radiology and oncology (Ljubljana), 2020)
Vulvar cancer accounts for 3%5% of malignant diseases of the female genital tract. The Slovenian incidence rate is 5.5/100,000, which means 57 new cases per year. The most common histological type (90%) is squamous cell carcinoma. Based on etiology, it can be classified into the first type which correlates with human papillomavirus (HPV) infection and the second type which is not associated with HPV. The most common and long-lasting symptom of vulvar cancer is pruritus. The preferred diagnostic procedure to confirm the diagnosis is a punch or incision biopsy. Surgery in combination with radiotherapy is the standard treatment for vulvar cancer. Sentinel lymph node biopsy with lymphoscintigraphy is now a standard part of surgical treatment. Chemotherapy is a palliative treatment option. Conclusions. Vulvar cancer is a rare disease. Because of the pathogenesis, surgery and radiotherapy are the main treatment modalities. The sentinel node biopsy (SNB) represents a contemporary approach to the vulvar cancer treatment and significantly reduces morbidity. Improvements in treatment of vulvar cancer contributed to the decrease of mortality among Slovenian women.
Keywords: biopsija varnostne bezgavke; kirurško zdravljenje; limfoscintigrafija; rak (medicina); zunanje spolovilo